Between Separation and Symbiosis South Eastern European Languages and Cultures in Contact - Joseph, Brian D.; Kisilier, Maxim L.; Konior, Daria V.; Kozak, Vyacheslav V.; Makarova, Anastasia L.; Morozova, Maria S.; Rusakov, Alexander Yu; Sobolev, Andrey N.; Sobolev, Andrey N. (Language contact and bilingualism ;, 2021)
The book deals in detail with previously understudied language contact settings in the Balkans (South East Europe) that present a continuum between ethnic and linguistic separation and symbiosis among groups of people. The studies in this volume achieve several aims: they critically assess the Balkan Sprachbund theory; they analyse general contact theories against the background of new, original, representative field and historical Greek, Albanian, Romance, Slavic and Judesmo data; they employ and contribute to recent methods of research on linguistic convergence in bilingual societies; they propose new general assessments of extra- and intralinguistic factors of Balkanization over the centuries; and they outline prospects for future research. The factors relevant to contact scenarios and linguistic change in the Balkans are identified and typologized through models such as those related to a balanced or unbalanced (socio)linguistic situation.